Numerical Analysis on Post-Fire Resistance of High-Strength Circular CFST Stub Column in Axial Compression - Hu, Jie; Li, Wei (Frontiers in Built Environment, 2022)
Concrete-filled steel tubular (CFST) structures using high-strength materials have been increasingly used in civil engineering due to their exceptional mechanical performance. A comprehensive numerical analysis was performed in this study, where a finite element model was established for CFST stub column using high-strength materials with consideration of fire and load combinations. The influence of critical parameters to the resistance in axial compression were analyzed based on the verified model, including the fire exposure time, the axial load level, the confinement factor, etc. The results showed that the residual resistance of high-strength CFST column in axial compression decreased with the increase of axial load level and fire exposure time, while it increased with the increase of material strength.